Offender insight into Australian stolen goods markets from 2002–2017: the DUMA survey as a 16-year window into property crime offenders’ target selections and disposal - Clare, Joseph (Psychology, crime & law, 2024)
Since 2002, seven iterations of the Drug Use Monitoring in Australia (DUMA) programme survey have asked arrested offenders about their stealing behaviours, including questions relating to stolen goods target selection and disposal. Throughout this same time period, stealing and domestic burglary rates in Australia have steadily declined. This paper examines the DUMA data with these high-level acquisitive crime trends in mind. Survey findings point to offenders having shifted away from stealing increasingly devalued electronic consumer goods for resale purposes, and toward stealing increasingly expensive food and clothing for personal consumption. This is consistent with what would be expected according to Consumer Price Index data, the opportunity-based CRAVED framework, and offender domain expertise. Applied and theoretical implications are discussed.